Effects of the oriental herbal medicine Bofu-tsusho-san in obesity hypertension: A multicenter, randomized, parallel-group controlled trial (ATH-D-14-01021.R2). Issue 1 (May 2015) - Azushima, Kengo; Tamura, Kouichi; Haku, Sona; Wakui, Hiromichi; Kanaoka, Tomohiko; Ohsawa, Masato; Uneda, Kazushi; Kobayashi, Ryu; Ohki, Kohji; Dejima, Toru; Maeda, Akinobu; Hashimoto, Tatsuo; et al.
Abstract Objective There is no clinical evidence that supports the benefit of integrative medicine, defined as combination therapy of oriental and western medicine, on obesity-related hypertension. This study evaluates the efficacy of Bofu-tsusho-san (BOF), an oriental herbal medicine, on the ambulatory blood pressure (BP) profile in hypertensive patients with obesity. Methods The study design was a multicenter, randomized, open-label, parallel-group controlled trial in 107 hypertensive patients with obesity. Participants were randomly assigned to receive either the conventional control therapy or BOF add-on therapy. In both groups antihypertensive therapy was aimed at achieving the target clinic BP. The primary outcome was change in the ambulatory BP profile from baseline to 24 weeks after randomization. Results Daytime systolic BP variability, an important parameter of ambulatory BP profile, was decreased in the BOF group, and the difference in the changes in daytime systolic BP variability was significant between the BOF and control group (Control vs BOF; the change from baseline in daytime systolic BP variability, 1.0 ± 3.3 vs −1.0 ± 3.3%; p = 0.006). Conclusion The BOF add-on therapy effectively improved the ambulatory BP variability. This is the first report suggesting that an integrative medicine approach may exert favorable effects on obesity-related hypertension compared with conventional pharmaceutical treatment. Clinical trial registration UMIN000003878.